Coagulation and Fibrinolysis in Kidney Graft Rejection - Stallone, Giovanni; Pontrelli, Paola; Rascio, Federica; Castellano, Giuseppe; Gesualdo, Loreto; Grandaliano, Giuseppe (Frontiers in Immunology, 2020)
Coagulation system is currently considered an integrated part of innate immunity. Clotting activation in response to bacterial surface along with complement cascade priming represents the first line of defense against pathogens. In the last three decades we learned that several coagulation factors, including factor II or thrombin and factor X, can interact with specific cell surface receptors activated by an unusual proteolytic mechanism and belonging to a novel class of G protein coupled receptors known as protease activate receptors (PAR). PARs are expressed by a variety of cells, including monocytes, dendritic cells, endothelial cells, and may play a key role in the modulation of innate immunity and in the regulation of its interaction with the adaptive branch of the immune system. Also the fibrinolytic system, which activation is controlled by coagulation, can interact with innate immunity and it is a key modulator of extracellular matrix deposition eventually leading to scarring and fibrosis. In the setting of kidney transplantation, coagulation and fibrinolytic systems have been shown to play key roles in the ischemia-reperfusion injury featuring delayed graft function and in the pathogenesis of tissue damage following acute and chronic rejection. In the present review we aim to describe the mechanisms leading to coagulation and fibrinolysis activation in this setting and their interaction with the priming of the innate immune response.